SAT0302 SINGLE-PORT THORACOSCOPIC SYMPATHICOTOMY IS VERY EFFECTIVE FOR TREATMENT RESISTANT RAYNAUD'S PHENOMENON: A ONE MONTH FOLLOW-UP. (June 2019) - Roon, Anniek van; Kuijpers, Michiel; Zande, Saskia van de; Abdulle, Amaal Eman; Roon, Arie Van; Bos, Reinhard; Bouma, Wobbe; Klinkenberg, Theo; Bootsma, Hendrika; Dejongste, Mike; Mariani, Massimo; Smit, Andries; et al.
Abstract : Background: In some patients, Raynaud's Phenomenon (RP) symptoms prove resistant to conventional vasodilatory treatment. Thoracic sympathectomy is shown to be effective as treatment of RP, but is associated with surgical burden. During this procedure, the sympathetic nerve traversing to the upper extremity is dissected, subsequently leading to vasodilatation. In our centre, single-port thoracoscopic sympathicotomy (SPTS) has been developed, a minimally invasive technique, extensively limiting surgical burden. [1] Objectives: To evaluate SPTS feasibility and efficacy after one month in patients with treatment resistant RP. Methods: In this study RP patients were their own controls, as they received an unilaterally left sided sympathicotomy. The effects of the SPTS was assessed at baseline and one month after the procedure. Perfusion of the hand was assessed using a cooling and recovery procedure, and laser speckle contrast analysis (LASCA) at room temperature of 23 degrees Celsius. The number and duration of RP attacks was reported over a two week period prior to reassessment by standard questionnaire. Results: Eight patients were included in the study, 6 male/2 female, with a median (IQR) age of 45.2 (30.2–55.3) years, body mass index of 23.9 (23.4–26.8) kg/m 2, and RP duration of 7.0 (2.5–14.3) years. Five patients suffered from primary RP, and three patients had RP secondary to connective tissue disease (CTD) [mixed CTD (n=2) and limited cutaneous systemic sclerosis (n=1)]. All patients were very satisfied with the results and the number of attacks in the left hand decreased (p=0.018). After surgery an unilateral improvement in left hand perfusion was observed during the cooling and recovery procedure (p=0.008, figure 1 ), and in the fingertips with LASCA (p=0.023). No serious adverse events occurred. Conclusion: SPTS, a minimally invasive technique, appears to be feasible and effective in improving hand perfusion in patients with RP after one month. Although these results are promising, long-term efficacy needs to be established and therefore follow-up is on-going. Reference: [1] Kuijpers M, Klinkenberg TJ, Bouma W, DeJongste MJ, Mariani MA. Single-port one-stage bilateral thoracoscopic sympathicotomy for severe hyperhidrosis: prospective analysis of a standardized approach. J Cardiothorac Surg2013;8:216-8090-8-216. Disclosure of Interests: Anniek van Roon: None declared, Michiel Kuijpers: None declared, Saskia van de Zande: None declared, Amaal Eman Abdulle : None declared, Arie Van Roon: None declared, Reinhard Bos Grant/research support from: SUN Pharma, Wobbe Bouma: None declared, Theo Klinkenberg: None declared, Hendrika Bootsma Grant/research support from: Unrestricted grants from Bristol-Myers Squibb and Roche, Consultant for: Roche, Bristol-Myers Squibb, Novartis, Medimmune, Union Chimique Belge, Speakers bureau: Bristol-Myers Squibb, Novartis, Mike DeJongste: None declared, Massimo Mariani: None declared, Andries Smit Shareholder of: Has been co-founder, and is still shareholder of Diagnoptics Technologies, the company which developed the AGE reader., Douwe J Mulder Grant/research support from: My University has received research grants for my research from: Boehringer Ingelheim and Actelion, Speakers bureau: My University has received speakers fee from: Sanofi